Sosialisasi Seminar Teknologi Pengendalian Pencemaran Udara - mulya, widya -; Pratama, iin; Adolf Liku, James Evert (EUNOIA, 2023)
Air pollution is the entry or inclusion of substances, energy and/or other components into the ambient air so that the quality of the ambient air drops to a certain level which causes the ambient air to be unable to fulfill its function (Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.15/ MENLHK/SETJEN/KUM.1/4/2019). Particulate Matter (PM 2.5) are airborne particles that are smaller than or equal to 2.5 µm (micrometer). PM 2.5 in Indonesia in 2022 is reported to be the 26th worst out of 131 countries globally, Indonesia's daily PM 2.5 concentration level in 2022 reaches 30.4 ugram/m³ (released by IQAir, a Swiss-based technology company). Air pollution control is a series of processes and technical approaches to eliminate or reduce the toxic level of certain compounds in exhaust gases, so that they do not exceed the established emission quality standards. Proper control of air pollution requires technical requirements that must be met in the construction of a waste to energy processing unit which requires an assessment at the beginning of the planning as well as the selection of control technology (national and international standards). The selection of air pollution control technology is based on consideration of the parameters being processed, selection of equipment (external parameters and characteristics of the equipment), system design (equipment and instruments). Particulate control technology consists of gravity, centrifugal, electrostatic, impaction, interception, diffusion processes. While gas control technology consists of adsorption, absorption, condensation, combustion processes. Keywords: Technology, Air Pollution Control.